Contribution to the taxonomy of Poecilimon bosphoricus species group (Orthoptera: Phaneropteridae): two new species from its core range - Chobanov, Dragan P.; Kaya, Sarp; Çiplak, Battal (Zootaxa, 2015)
The Poecilimon bosphoricus species group, representing the most diverse lineage of the bushcricket genus Poecilimon, has been studied in the Basin of Marmara Sea. Two new species, P. warchalowskae sp. n. and P. canakkale sp. n., are described morphologically and acoustically in comparison to their related taxa of the P. bosphoricus species group. Song type and morphology of the new species suggests that they are related to P. turcicus, P. turciae and P. athos and each of these five species can be distinguished by their specific male cerci. The diagnoses are supplemented with comparative figures of morphology and song. Additionally, a short account is given on the synonymy of P. anatolicus with P. sureyanus.